PENGUATAN PROFESIONALISME SDM SISWASMK MULIA BUANA PARUNG PANJANGDALAM MENYIKAPI DINAMIKA ERA INDUSTRI MODERN - Yanurianto Yanurianto; Lilis Suryani; Ratnawati Ratnawati (Jurnal Pengabdian Tangerang Selatan [JURANTAS], 2026)
The modern industrial era demands human resources who are not only technically competent, but also possess high professionalism in facing the dynamics of technological change and labor market demands. This Community Service Program aims to strengthen the professionalism of students at SMK Mulia Buana Parung Panjang through comprehensive training covering digital literacy, financial management, professional work ethics, and adaptation to Industry 4.0 technology. The activity was conducted on March 7-9, 2026 using participatory learning methods combining interactive lectures, practical workshops, case studies, and workplace simulations. Program participants were 48 students from grades XI and XII selected based on learning motivation and post-graduation career plans. Evaluation results showed a significant increase in understanding of professionalism concepts with average pre-test scores of 63.8 increasing to 84.2 on post-test, indicating a 32% improvement in material mastery. Professional attitude evaluation through observation showed 89% of participants were able to demonstrate better professional behavior in various work situation simulations. Satisfaction survey showed 93% of participants rated the program as very beneficial and 85% felt more prepared to face modern workplace demands. This program proves that structured intervention in professionalism development can effectively prepare vocational high school students to face the dynamics of the modern industrial era with more confidence and competence.